1995
DOI: 10.1097/00000542-199511000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Measured Context-sensitive Half-times of Remifentanil and Alfentanil

Abstract: The measured context-sensitive half-times were in close agreement with the context-sensitive half-times previously modelled for these drugs. The results of this study confirm the value of the context-sensitive half-time in describing drug offset compared to the terminal elimination half-life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(109 citation statements)
references
References 8 publications
0
102
0
7
Order By: Relevance
“…The context-sensitive half-time of remifentanil is constant and independent of duration of drug administration when administered for up to 6 hours [3], but does this situation change when remifentanil is given for days rather than hours? One study looked at the pharmacodynamic offset of remifentanil at various time points over 3 days in ICU patients and found that the offset time was constant over this period [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The context-sensitive half-time of remifentanil is constant and independent of duration of drug administration when administered for up to 6 hours [3], but does this situation change when remifentanil is given for days rather than hours? One study looked at the pharmacodynamic offset of remifentanil at various time points over 3 days in ICU patients and found that the offset time was constant over this period [5].…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil is metabolised by non-specific plasma esterases and is therefore independent of organ function [2]. Remifentanil is rapidly metabolised and has a context-sensitive half-time of about 2 to 3 min that is independent of duration of infusion [3]. These features of remifentanil make it an ideal agent for use in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the short duration of effect is the redistribution of thiopental from highly perfused tissues, particularly the CNS, to other tissues [258]. Clinical studies with anesthetic drugs revealed that the elimination half-life often failed to predict the loss of anesthetic effect (recovery from anesthesia) [259,260]. For example, the half-life of loss of anesthetic effect was 5 and 50 min for remifentanil and alfentanil, respectively, while the corresponding elimination half-lives were 20 and 110 min [259].…”
Section: Pharmacokinetic Half-life Vs Pharmacologic Halflifementioning
confidence: 99%
“…Clinical studies with anesthetic drugs revealed that the elimination half-life often failed to predict the loss of anesthetic effect (recovery from anesthesia) [259,260]. For example, the half-life of loss of anesthetic effect was 5 and 50 min for remifentanil and alfentanil, respectively, while the corresponding elimination half-lives were 20 and 110 min [259]. Sufentanil, with an elimination half-life of 577 min, had a shorter half-life of anesthetic recovery compared to alfentanil, whose half-life of loss anesthesia was 50 min.…”
Section: Pharmacokinetic Half-life Vs Pharmacologic Halflifementioning
confidence: 99%
“…All opioids depress the central nervous, respiratory and cardiovascular system (particularly meperidine), and they increase the intrabiliary pressure, decrease gastric motility and cause nausea/vomiting and constipation. Though sufentanil, alfentanil and remifentanil are superior to fentanyl, fentanyl is a good choice with the less cost [8,9]. …”
Section: Opioidsmentioning
confidence: 99%